Modify Indonesian Catholic Religious Education from Mono-Religious to Interreligous Education - Antonius Virdei Eresto Gaudiawan; Tabita Kartika Christiani; Arqom Kuswanjono (P3TK, Sanata Dharma University, 2023)
Catholic religious education is an educational process that helps Catholic students grasp the knowledge of the Christian life and identity. In Indonesia, national education law pushes students to learn their religion. Religious education then becomes a mono-religious education that does not suit the Indonesian plurality. It will elevate exclusivism. Indonesian Catholic religious education promotes respect, dialogue, and collaboration between religious adherents. The foundation for this effort is Catholic respect toward other religions, explicitly stated in the declaration of Nostra Aetate. Every grade has a topic that introduces different cultures and religions. It is the application of Indonesian Catholic religious education to educate students to respect other beliefs. It is a good start for multicultural education, and at the same time, it raises questions about the probability of modifying a mono-religious education into an interreligious one. This research was conducted in the diocese of Surabaya, while Jombang, Blitar, and Surabaya were chosen as the diocese's representatives. Interviews with Catholic religious teachers used a semi-structured mode. These are some findings from this research. Practices of Catholic religious education in Indonesia open the possibility of modifying a mono-religious education becomes interreligious education. It needs teachers' commitment and school policy that allows the teacher to modify the curriculum. The teachers' creativity to alter the curriculum needs the principal's goodwill. It also needs reformation from every aspect of school as a social system to support multicultural education. On the other side, the environment outside the school is hoped to give positive support for the reformation by giving broader experience. Through this process, Catholic religious education in Indonesia fulfill its destiny to cultivate faith and promote respect toward other religions.